2006
DOI: 10.1016/j.apm.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Gas-powder flow in blast furnace with different shapes of cohesive zone

Abstract: With high PCI rate operations, a large quantity of unburned coal/char fines will flow together with the gas into the blast furnace. Under some operating conditions, the holdup of fines results in deterioration of furnace permeability and lower production efficiency. Therefore, it is important to understand the behaviour of powder (unburnt coal/char) inside the blast furnace when operating with different cohesive zone (CZ) shapes. This work is mainly concerned with the effect of cohesive zone shape on the powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…17) It was found that the Re p values varied from 0.4 to 500 for the gas velocities of 0.3-9.6 m/s and particle size in the range 21 < d p ≤752 μm. Therefore, the value of C D = 10/(Re p 1/2 ) was used in Eq.…”
Section: Characterization Of Dust After Wear Trialsmentioning
confidence: 99%
“…17) It was found that the Re p values varied from 0.4 to 500 for the gas velocities of 0.3-9.6 m/s and particle size in the range 21 < d p ≤752 μm. Therefore, the value of C D = 10/(Re p 1/2 ) was used in Eq.…”
Section: Characterization Of Dust After Wear Trialsmentioning
confidence: 99%
“…[1] For a layered CZ treatment, the CZ is numerically modeled as a region comprising impermeable or low-permeability iron-bearing material layers and highly permeable coke layers. [25][26][27][28][29][30] The existence of this layered structure makes modeling more difficult. For example, to treat liquid flow in the layered CZ, the so-called force balance model [18,31,32] had to be modified to allow the liquid to traverse the impermeable cohesive layers.…”
Section: An Ironmaking Blast Furnace (Bf) Is a Multiphasementioning
confidence: 99%
“…11. 114) A powder accumulation region can also be identified in the lower part of the BF. For different CZ shapes, the powder distribution shows significant differences.…”
Section: Model Findingsmentioning
confidence: 94%